Towards the synthesis of heterocycle containing natural products - Dexter, Hannah (2017)
Chapter 1 gives an introduction to ribosomally synthesised and post-translationally modified peptides. The different classes of this group of natural products are described. Examples of linear azol(in)e-containing peptides and cyanobactins are given, along with more detail about these classes of peptides and examples of their chemical synthesis. Chapter 2 explains the importance of the natural product goadsporin 64, along with the retrosynthesis and a review of methods to synthese oxazoles, thiazoles and dehydroalanines. The first total synthesis of goadsporin 64 is then reported, demonstrating the use of rhodium catalysis to construct the four oxazole rings. Synthesis of the N-terminal fragment 78 validated methods for incorporating the sensitive enamide functionality, and removal of the necessary protecting group. These methods were then applied to the full structure to complete the total synthesis. Chapter 3 describes work carried out towards the total synthesis of the wewakazole natural products, again using rhodium catalysis methodology. The structures of wewakazole A 65 and wewakazole B 66 share a largely peptidic fragment 267, differing only by the bis-oxazole fragments 266 and 268, allowing the synthesis of two natural products via three main fragments. Reported herein is the synthesis of the bis-oxazole fragments 266 and 268 of wewakazole A 65 and B 66.